2015
DOI: 10.3109/10826084.2015.1074694
|View full text |Cite
|
Sign up to set email alerts
|

Daily Reports of Positive and Negative Affect and Alcohol and Marijuana Use Among College Student and Nonstudent Young Adults

Abstract: Background Daily affect and substance use covary among college students, but little is known about these associations among young adults not in college. Objectives The current pilot study examines associations between positive and negative affect and alcohol and marijuana use, with a focus on differences between college student and non-student young adults. Methods High school seniors completed a baseline survey during the spring of 2012 and were then randomly selected to participate in an intensive measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
4
14
0
1
Order By: Relevance
“…The average number of reports completed was around 10 out of the 14 possible days. These compliance rates are similar to those reported previously by Patrick and colleagues (2016) with a sample of recent high school graduates. They found a compliance rate of 82.7% for at least one daily survey, 75% for at least half of days, and 67% for at least 10 days.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The average number of reports completed was around 10 out of the 14 possible days. These compliance rates are similar to those reported previously by Patrick and colleagues (2016) with a sample of recent high school graduates. They found a compliance rate of 82.7% for at least one daily survey, 75% for at least half of days, and 67% for at least 10 days.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, there has only been one prior investigation examining the drinking behavior of nonstudents utilizing a daily diary approach (Patrick, Yeomans-Maldonado, & Griffin, 2016); however, this study was restricted only to recent high school graduates, and thus, findings regarding generalizability to other nonstudents remain limited. While there have been a handful of investigations of daily drinking patterns with noncollege populations (e.g., Goldman, Greenbaum, Darkes, Brandon, & Del Boca, 2011; Lau-Barraco, Braitman, Linden-Carmichael, & Stamates, 2016; Lau-Barraco, Braitman, Stamates & Linden-Carmichael, 2016a, 2016b; Reich, Cummings, Greenbaum, Moltisant, & Goldman, 2015), these investigations used a retrospective method via the timeline follow-back (TLFB) procedure, which has been shown to yield less accurate reports of drinking than daily approaches (Carney, Tennen, Affleck, Del Boca, & Kranzler, 1998).…”
mentioning
confidence: 99%
“…Negative or positive states of mood were found to be associated with heavier or lighter drinking depending on the individual’s traits and environmental characteristics that these emotions are combined with [57, 61, 63, 72, 82, 86, 93]. Heavy drinking is particularly likely to occur on days when a lot of negative emotion or negative interpersonal events are experienced for individuals who are socially anxious [80], have low self-esteem, high shame or high neuroticism [54, 73, 77], have high social support [43], are less educated [61], have high drinking-to-cope motives [78, 82] or have low drinking to conform motives [78].…”
Section: Resultsmentioning
confidence: 99%
“…Heavy drinking is particularly likely to occur on days when a lot of negative emotion or negative interpersonal events are experienced for individuals who are socially anxious [80], have low self-esteem, high shame or high neuroticism [54, 73, 77], have high social support [43], are less educated [61], have high drinking-to-cope motives [78, 82] or have low drinking to conform motives [78]. In contrast, studies suggested that people with low shame [73], non-students [86], students not affiliated with a sorority [72], men with low attention spans [57] and women with high attention spans [57] are less likely to engage in heavy drinking on days they have negative mood. Also, individuals with low social anxiety or low drinking to cope motives tend to drink less on days they experience negative interpersonal interactions [78, 80].…”
Section: Resultsmentioning
confidence: 99%
“…Existen datos que demuestran la asociación entre distintas características del grupo de población adolescente y el consumo de alcohol y otras drogas. Por ejemplo, los jóvenes que estudian bachillerato (Patrick, Yeomans-Maldonado y Griffin, 2016) tienen mayor prevalencia de consumo de alcohol, en los años que dura la escolarización, que los no estudiantes, que presentan más consumo de marihuana (Johnston, O'Malley, Miech, Bachman y Schulenberg, 2012;O'Malley y Johnston, 2002). Sin embargo, a largo plazo, las personas que no cursaron bachillerato tienden a tener mayores consumos de alcohol y más problemas de uso de otras sustancias en la etapa adulta, comparados con aquellos que sí estudiaron (Lanza y Collins, 2006;Patrick et al, 2016;White, Labouvie y Papadaratsakis, 2005).…”
unclassified